Is it important to Study Mind, Body and Soul in Trinity of Life to Treat a Patient in Homeopathy? (Homoeopathy for All, 2023)
Life is composed of body, mind,  and spirit. This is the trinity of life.  Body and tissues are not life they  are only the channels through which  life functions. The material body  derives its life from an immaterial,  autocratic, spiritual, dynamic thing  called ‘VITAL FORCE’. It maintains  the harmony of life producing  normal sensations and functions.
Keywords: Body; Soul; Patient